2012
DOI: 10.1038/jid.2011.472
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Gene Expression Subsets of Diffuse Cutaneous Systemic Sclerosis Are Stable in Serial Skin Biopsies

Abstract: Skin biopsy gene expression was analyzed by DNA microarray from 13 dSSc patients enrolled in an open label study of rituximab, 9 dSSc patients not treated with rituximab, and 9 healthy controls. These data recapitulate the patient ‘intrinsic’ gene expression subsets described previously including proliferation, inflammatory, and normal-like groups. Serial skin biopsies showed consistent and non-progressing gene expression over time, and importantly, the patients in the inflammatory subset do not move to the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
181
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 148 publications
(209 citation statements)
references
References 37 publications
24
181
2
2
Order By: Relevance
“…Given the repeatedly observed clinical and molecular heterogeneity in SSc patients across multiple independent cohorts (8,(10)(11)(12), the robustness of the SSc signatures identified in our analysis is unexpected and significant. Until now, the lack of such a robust signature has hampered development of novel diagnostics and prognostics for monitoring SSc patients in clinics.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Given the repeatedly observed clinical and molecular heterogeneity in SSc patients across multiple independent cohorts (8,(10)(11)(12), the robustness of the SSc signatures identified in our analysis is unexpected and significant. Until now, the lack of such a robust signature has hampered development of novel diagnostics and prognostics for monitoring SSc patients in clinics.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies using whole-genome expression profiles of SSc skin biopsies have demonstrated the molecular heterogeneity between patients with SSc (10-12). Based on this heterogeneity, SSc patients can be classified by their intrinsic subset (10,11). Therefore, we explored whether there is any relationship between 4S and the intrinsic subsets.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations